Epibiontic life on intertidal Setaphyes kielensis and S. dentatus (Kinorhyncha, Pycnophyidae) from Sylt, North Sea, Germany, with a description of a new species of Trematosoma (Ciliophora, Acinetidae) and a redescription of Cothurnia buetschlii (Ciliophora, Vaginicolidae) - Neuhaus, Birger; Lu, Borong; Yamasaki, Hiroshi; González-Casarrubios, Alberto (Zootaxa, 2023)
Specimens of two species of Kinorhyncha, Setaphyes dentatus and S. kielensis, were collected in 1988, 1998, and 2016 at two intertidal sites on the island of Sylt, North Sea, and investigated as preserved material by light microscopy and scanning electron microscopy for their epibionts. One species of Acinetidae (Suctoria), one species of Vaginicolidae (Peritrichia), and two species of bacteria were traced. The most abundant ciliate species with 705 specimens was Trematosoma husselae sp. nov. occurring with 1–46 specimens on a basibiont, mainly on the ventral side and here especially on segment 1. Cothurnia buetschlii was found as 14 specimens. Trematosoma husselae sp. nov. agreed with T. amphiasci and T. pusilla in the calyciform shape of the lorica and with most species in the general size of the body except for the much larger T. constricta and T. pusilla. The new species could be distinguished from T. amphiasci, T. complatana, T. constricta, T. falcata, T. ovata, and T. pusilla by the short length of its stalk and agreed with T. bocqueti and T. rotunda in this character. Cothurnia buetschlii was redescribed for the first time after the descriptions by Zelinka (1914, 1928).